2018
DOI: 10.1002/cad.20227
|View full text |Cite
|
Sign up to set email alerts
|

Steps Toward Peace and Violence Prevention Across Generations: The Potential of Early Child Development in the Context of the 2030 Sustainable Development Goals

Abstract: This special issue of New Directions in Child and Adolescent Development features four review articles from authoritative leaders in the field. These articles highlight how far our field has come over the past five decades, as well as how much further effort is needed to refine, adapt, and implement - in a sustainable fashion - responsive parenting and nurturing care programs of proven value across the globe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A large body of research has shown that violence and maltreatment against children can be detrimental to children’s outcomes, especially in developing countries where a significant percentage of children are at risk of not reaching their developmental potential (Black et al, 2017; Leckman & Britto, 2018). In particular, exposure to physical punishment and other forms of household violence has been shown to predict a host of negative outcomes across the lifespan, including behavioral problems such as aggression, antisocial behavior, low self‐esteem, and mental health problems (Gershoff & Grogan‐Kaylor, 2016; Pinquart, 2017).…”
Section: Figurementioning
confidence: 99%
“…A large body of research has shown that violence and maltreatment against children can be detrimental to children’s outcomes, especially in developing countries where a significant percentage of children are at risk of not reaching their developmental potential (Black et al, 2017; Leckman & Britto, 2018). In particular, exposure to physical punishment and other forms of household violence has been shown to predict a host of negative outcomes across the lifespan, including behavioral problems such as aggression, antisocial behavior, low self‐esteem, and mental health problems (Gershoff & Grogan‐Kaylor, 2016; Pinquart, 2017).…”
Section: Figurementioning
confidence: 99%
“…Finally, nurturing care interventions in LMICs have been mainly implemented in low-income populations and populations at risk for undernutrition and rarely in other adverse contexts, such as those affected by armed conflicts and forced migration. In recent years, researchers have brought attention to the value of nurturing care interventions in fragile and conflict contexts and their potential to reduce violence and promote peace (4,90). The Early Childhood Peace Consortium is one such innovative approach aimed at peacebuilding through investment in early child development (91).…”
Section: Discussionmentioning
confidence: 99%
“…In low-and middle-income countries (LMICs), over 250 million children under age five are not achieving their developmental potential due to adverse living environments, such as chronic poverty, poor nutrition and sanitation, violence, and inadequate learning opportunities (1). As emphasized in multiple United Nations Sustainable Development Goals, child development has been recognized as playing a key role in the long-term development and well-being of the society at large (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) ECD serves as the foundation for sustainable development as it has a direct effect on the overall development of children and the adults they will become. 3) Thus, ensuring that every child develops to the maximum extent possible and achieves their full developmental potential through multi-disciplinary investments in ECD has been prioritized by governments and United Nations agencies including the United Nations Children's Fund (UNICEF) and the World Health Organization. 4,5) Developmental screening is a crucial component of ensuring ECD, as it allows the early identification of any abnormal neurodevelopmental process.…”
Section: Introductionmentioning
confidence: 99%